Staff Guidance Note on the Use of Fund Resources for Budget Support. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper proposes that the Fund establish an administered account and a subaccount under the Framework Instrument for Selected Fund Activities (the 'SFA'), to enhance the new external financing architecture for capacity building and related Fund activities. The specific accounts proposed to be established are: (1) an administered account for interim holdings of voluntary contributions for Fund activities, that would primarily accommodate contributions from donors for Fund activities that are planned but not yet fully developed ('The Interim Holding Administered Account,' hereinafter, the 'Holding Account'); and (2) a Subaccount for the administration of selected smaller-scale capacity building and related activities (the 'Catch-All Subaccount') under the SFA Instrument, which would facilitate the administration of external funds for smaller, one-off projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Turkey